Estudio de viabilidad financiera, ambiental y energética para la sustitución de una de las calderas de búnker por una de biomasa en la Planta San Rafael de la empresa Cargill Costa Rica - Romero-Arias, Jorge Alberto (Instituto Tecnológico de Costa Rica, 2018)
This investigation is focused on the viability of the installation of a biomass boiler system to reduce the environmental impact and dependence on fuel delivery while also gaining an annual savings for the company of Cargill San Rafael Plant (PIPASA). The project begins with a data collection of fuel oil and steams demands to measure the plant’s energy consumption and also the environmental impact it generates and the high annual payments for fuel. It allows to consider different scenarios to propose a more viable solution. The average energy consumption of the plant is 10 922 350 MJ, an average consumption of 269 144 L of monthly bunker, 10 050 metric tons of global warming gases emitted per year. The annual fuel purchase is $1 617 535 and a monthly consumption of 7 tons of steam per hour which is obtained from the performance of a dual schedule to simultaneously observe the work of the steam consuming equipment. The project it’s based on a comprehensive level with a mixed source design (documentary and field). Once the consumption mentioned above is established, we proceeded to analyze the possible fuels to replace the bunker, which are LPG and biomass (pellet and chip). Then the necessary capacity of the boiler to be installed was established (9-ton hour steam boiler), considering consumption peaks and the low consumption of the plant.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018
Keywords: Sistemas; Generadores de vapor; Biomasa; Combustibles; Agua; Gases; Efecto invernadero; Ahorro energético; Mejoramiento; Research Subject Categories::TECHNOLOGY::Engineering mechanics